Unencumbered Pol β lyase activity in nucleosome core particles. Issue 15 (11th July 2017) - Rodriguez, Yesenia; Howard, Michael J.; Cuneo, Matthew J.; Prasad, Rajendra; Wilson, Samuel H.
Abstract: Packaging of DNA into the nucleosome core particle (NCP) is considered to exert constraints to all DNA-templated processes, including base excision repair where Pol β catalyzes two key enzymatic steps: 5′-dRP lyase gap trimming and template-directed DNA synthesis. Despite its biological significance, knowledge of Pol β activities on NCPs is still limited. Here, we show that removal of the 5′-dRP block by Pol β is unaffected by NCP constraints at all sites tested and is even enhanced near the DNA ends. In contrast, strong inhibition of DNA synthesis is observed. These results indicate 5′-dRP gap trimming proceeds unperturbed within the NCP; whereas, gap filling is strongly limited. In the absence of additional factors, base excision repair in NCPs will stall at the gap-filling step.